An efficient merging scheme for prescribed skew clock routing. - Chaturvedi, R. (IEEE Transactions on VLSI systems)
In ultra-deep submicron very large-scale integration (VLSI) designs, clock network layout plays an increasingly important role on determining circuit quality indicated by timing, power consumption, cost, power-supply noise, and tolerance to process variations. In this brief, a new merging scheme is proposed for prescribed nonzero skew routings which are useful in reducing clock cycle time, suppressing power-supply noise, and improving tolerance to process variations. This technique is simple and easy to implement for practical applications. Experimental results on benchmark circuits with both buffered and unbuffered routings exhibit large improvement on wirelength and buffer cost compared with other existing works.